2004
DOI: 10.1126/stke.2422004re10
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Proteins: A Number of Functions for a Numbered Protein

Abstract: Many signal transduction events are orchestrated by specific interactions of proteins mediated through discrete phosphopeptide-binding motifs. Although several phosphospecific-binding domains are now known, 14-3-3s were the first proteins recognized to specifically bind a discrete phosphoserine or phosphothreonine motif. The 14-3-3 proteins are a family of ubiquitously expressed, exclusively eukaryotic proteins with an astonishingly large number of binding partners. Consequently, 14-3-3s modulate an enormous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 119 publications
1
112
0
5
Order By: Relevance
“…14-3-3 proteins are phosphopeptide-binding proteins that participate in various signal transduction and regulatory processes by interacting with diverse types of target proteins in a sequence-specific and phosphorylation-dependent manner [61]. In this study, the kinase motif [sxP, A1] also contains one of two types of 14-3-3 protein binding motifs, the mode II motif [RxxxsxP] [60].…”
Section: 6mentioning
confidence: 99%
“…14-3-3 proteins are phosphopeptide-binding proteins that participate in various signal transduction and regulatory processes by interacting with diverse types of target proteins in a sequence-specific and phosphorylation-dependent manner [61]. In this study, the kinase motif [sxP, A1] also contains one of two types of 14-3-3 protein binding motifs, the mode II motif [RxxxsxP] [60].…”
Section: 6mentioning
confidence: 99%
“…The 14-3-3 proteins function as homodimers and heterodimers to control the spatial and temporal activity of substrate proteins by regulating subcellular localization (Muslin and Xing, 2000;Nagata-Ohashi et al, 2004), binding partner proximity (Jones et al, 1995;Berruti, 2000;Van Der Hoeven et al, 2000) and by inducing conformational changes that can affect interactions between binding proteins and their substrates (Roy et al, 1998). In mammals, there are seven 14-3-3 isoforms, designated ␤ or ␣ (␤,␣), , , ␥, or ( , ), or ␦ ( ,␦), and /stratifin ( ) (Bridges and Moorhead, 2005). Multiple binding partners have been described for each 14-3-3 isoform; however, the functional relevance of these interactions has only been elucidated for a small subset of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of S910 and S935 within LRRK2 promotes binding of 14-3-3 proteins (19), a family of small 29-30 kDa acidic regulatory proteins, highly conserved and ubiquitously expressed in various tissues. The binding of 14-3-3 proteins results in various downstream effects, such as changes in structural conformations, kinase activity, and subcellular localization of the target proteins (20,21). Nichols et al (19) proposed a role for 14-3-3 proteins in regulating the cytoplasmic localization of LRRK2, whereas Li et al (12) observed protection from dephosphorylation of S935 after 14-3-3…”
mentioning
confidence: 99%